Strategic Management of Islamic Teaching for Strengthening Religious Moderation in Public Universities - Baedowi, Ahmad; Syukur, Fatah; Musyafak, Najahan; Faizah, Rohmatul; Hidayatulloh, M. Agung (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to explore the strategies for strengthening religious Moderation and national defences in the Islamic Religious Education (PAI) course, as implemented by Islamic Religious Education lecturers at the University of Indonesia. These strategies serve as a supplement to enhance students' understanding of moderate religious perspectives and deepen their national insight. This research employs a qualitative approach using a case study method conducted at the University of Indonesia. The data was obtained through in-depth interviews with PAI lecturers at UI, document analysis, and participatory observation. The data analysis process in this study consisted of data reduction, data display, and conclusion drawing. Data was reduced by selecting and categorizing relevant information obtained from interviews, document analysis, and participatory observations. The reduced data were then systematically presented in a narrative form to facilitate the interpretation process. The final stage involved drawing conclusions by identifying patterns, relationships, and meanings that emerged from the overall analyzed data. The findings indicate that the implementation of Islamic Religious Education at the University of Indonesia follows the regulations governing General Compulsory Courses (MKWU) as mandated by the government. The Islamic Religious Education course at UI is part of the Higher Education Personality Development Program (PPKPT) under the University Course Management, Directorate of Education, University of Indonesia. In practice, PAI at UI is not only taught through classroom lectures but also supplemented with treatments and enrichment activities such as religious studies, personality, and organizational capacity development (Religious Moderation and National Defense Student Movement). These efforts aim to enhance students' religious knowledge and understanding while simultaneously strengthening their national insight.